LA JERGA EN EL VOCABULARIO DE LOS ESTUDIANTES SEPTIMO Y OCTAVO DEL CENTRO EDUCATIVO COMUNITARIO JOSÉ ANTONIO PONTON ALAUSI PERIODO 2017-2018 - Valente Cepeda, Manuel (2019)
This research report, which is put into consideration and has been executed, consists of three fundamental stages for its entire fulfillment; the first stage called the Project Plan, which consisted in four chapters, it was fulfilled and had its corresponding approval by the commission for the Basic Education Career and the H. Directing Council of the Faculty of Education Sciences. Subsequently, the Project Report, the second stage, consists of four chapters that have also been prepared according to the scientific domain and research line of UNACH, Faculty and the institutional educational and pedagogical model, under the procedures of the Academic Regime Regulation and of the SGC, in this is detailed , more meticulous the proposed thing and through statistical data, that occupy the leading part of this stage, acquired by a population submitted to a survey, gave the guideline to be able to establish the conclusions of the study in relation to the analyzed variables: the jargon linguistic in the surveyed students and their vocabulary or communication; since it has been elaborated in the Project Report, the third and final stage of this Research work. Apart from that it is pointed out that during al this research time, there has been the willingness and collaboration of al those involved, especially the Bilingual Intercultural Educational Center “José Antonio Ponton”, through its Director and Teachers who supported the process, and also the fundamental support of the Basic Education Career teachers and the tireless advice of Dr. Jorge Fernandez Pino. Ph,D, Tutor and guide in this investigative work.